2020
DOI: 10.3389/fpls.2020.00844
|View full text |Cite
|
Sign up to set email alerts
|

Ex Ante Assessment of Returns on Research Investments to Address the Impact of Fusarium Wilt Tropical Race 4 on Global Banana Production

Abstract: The spread of Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4), causal agent of Fusarium wilt of banana (FWB), has been projected to reach 17% of the global banana-growing area by 2040 equaling 36 million tons of production worth over US$10 billion. This potential loss has fueled (inter)national discussions about the best responses to protect production and small-scale growers’ livelihoods. As part of a multi-crop ex ante assessment of returns on researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…These data encourage discussions on the current status of biosafety regulations and laws on the marketing of GM products that face some challenges because of the regulation of these products in several countries [162,163]. Furthermore, their outlook indicated that investments in GM banana plantations would bring few beneficiaries, given the assumption that countries with export-oriented banana production would not adopt GM varieties because of political and consumer concerns [138]. In this sense, it seems reasonable to invest more in improvements based on crossbreeding, considering that there are sources of resistance to Fusarium wilt caused by FOC R1 and FOC TR4, which enables the selection of resistant hybrids within the progeny generated.…”
Section: Main Methods and Tools Adoptedmentioning
confidence: 65%
See 3 more Smart Citations
“…These data encourage discussions on the current status of biosafety regulations and laws on the marketing of GM products that face some challenges because of the regulation of these products in several countries [162,163]. Furthermore, their outlook indicated that investments in GM banana plantations would bring few beneficiaries, given the assumption that countries with export-oriented banana production would not adopt GM varieties because of political and consumer concerns [138]. In this sense, it seems reasonable to invest more in improvements based on crossbreeding, considering that there are sources of resistance to Fusarium wilt caused by FOC R1 and FOC TR4, which enables the selection of resistant hybrids within the progeny generated.…”
Section: Main Methods and Tools Adoptedmentioning
confidence: 65%
“…Using an ex-ante quantitative risk index model, Staver et al [138] showed that investments in different research areas assessed to address the threat and projected losses from FOC TR4 would provide positive returns and contribute to a reduction in poverty. Moreover, there would be superior returns in poverty reduction, especially in Africa, in the face of investments in the research areas related to the conventional improvement of cultivars resistant to Fusarium wilt, as well as in the research area related to improving exclusion and surveillance, as well as measures to eradicate or contain the disease, with 850,000 and 807,000 people lifted out of poverty in each case, respectively.…”
Section: Main Methods and Tools Adoptedmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the disease distribution within fields and regions, hypotheses can be developed to understand the ways plant pathogens can be dispersed. The dynamics of the disease over time and information on the social and economic impact of a plant disease are key for implementing resources and efforts to guide strategies to manage plant diseases [ 41 ]. Regarding those assumptions, this work assessed the intensity, investigated the spatial and temporal dynamics, and estimated the yield and economic impact of FWB in 30 banana fields (94.6 ha) in six different production regions in Brazil.…”
Section: Discussionmentioning
confidence: 99%